Czynnik czasu w teorii i praktyce organizacji i zarządzania przedsiębiorstwem - Pilcer, Helena (The Factor of time in theory and practice of the enterprise organization and management, 2006)
The article presents the achievements of classic school in range of using time factor in theory and practice of management, and current continuation of focusing on them in today concepts, methodcs and tools used in management of enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 34-41